2020
DOI: 10.1007/s40620-020-00823-z
|View full text |Cite
|
Sign up to set email alerts
|

High mortality of CKD patients on hemodialysis with Covid-19 in Brazil

Abstract: The first case of the novel coronavirus disease (Covid-19) pandemic in Brazil was reported on February 26th, 2020, in São Paulo. On June 30th, Brazil ranked 2nd in the world in the number of cases, with 1.4 million victims officially reported and an average number of 37,600 new cases per day [Coronavirus disease case panel 2019 (COVID-19) in Brazil by the Ministry of Health. Available at: https ://covid .saude .gov.br/. Accessed June 27, 2020.]. Brazil is the third country in the world in the number of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
1
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 7 publications
6
45
1
10
Order By: Relevance
“…This is the rst national study of hemodialysis patients with COVID-19 in Lebanon. Our results con rm the high mortality rate of this vulnerable population, as described in several previous reports from other countries [14,17,19,20,22,23,26]. Our patients' death rate was estimated at 23.8%, very close to the 25%…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is the rst national study of hemodialysis patients with COVID-19 in Lebanon. Our results con rm the high mortality rate of this vulnerable population, as described in several previous reports from other countries [14,17,19,20,22,23,26]. Our patients' death rate was estimated at 23.8%, very close to the 25%…”
Section: Discussionsupporting
confidence: 90%
“…In the largest Chinese sample from Wuhan, death rate was estimated at 20% [13]. The Paris Region, Japan, the UK Renal Registry, the Scottish Renal Registry, the Belgian Society of Nephrology, Brazil, Germany, Italy, Spain and New York reported death rates in hemodialysis of 27.3%, 16% (at one week), 12.5%, 26.7%, 29.6%, 27.7%, 26.8%, 32%, 20% and 27% respectively [14][15][16][17][18][19][20][21][22][23]. Recently, the largest two studies conducted in Europe, the ERACODA (European Renal Association COVID-19 Database) and the ERA-EDTA Registry reported a death rate after 28 days of follow-up of 25% and 20% respectively [24,25].…”
mentioning
confidence: 99%
“…A study carried out in Zhongnan hospital, Wuhan, described diarrhea as the most frequent manifestation in these patients 52 . Another study reported gastrointestinal manifestation as the most important initial complaint among patients on dialysis treatment, and due to the atypical symptomatology, the authors emphasized the importance of individualized patient approach to optimize COVID-19 diagnostic accuracy in this peculiar group with uncertain prognosis [52][53][54] .…”
Section: Patients With Ckd In Dialytic Therapy and Covid-19mentioning
confidence: 99%
“…The Brazilian Society of Nephrology issued COVID-19 management recommendations in May 2020. 45 In a nationwide survey through June 2020, 12% of dialysis staff had confirmed or suspected COVID-19, with two reported deaths 11 . Cases and case fatality ratios among dialysis patients were much higher than in the general population, and higher still in regions such as the northeast and north with lower economic resources.…”
Section: Brazil (Roberto Pecoits-filho Curitiba)mentioning
confidence: 99%
“…1 Our panelists summarized national data for dialysis populations, based on registry reports, claims-based reports, or society surveys (Figure 2, Table 1), and contextualized these findings. [2][3][4][5][6][7][8][9][10][11][12][13] Predictably but sobering, per-population cases and deaths among dialysis patients vary by 10-to 100-fold, as in the general population (Figure 3). Common across countries, published center and regional experiences report lower infection risk among home dialysis patients, but also confirm that outcomes among infected persons are poor for both home and in-center dialysis patients, with case fatality ratios of at least one in ten for persons diagnosed by targeted testing.…”
Section: Introductionmentioning
confidence: 99%